Climate Risk, Legal Liability, and Portfolio Strategy: A Qualitative Review of Brown Assets as Hedging Instruments in High-Carbon Scenarios - Seger Santoso; Farah Qalbia (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review synthesizes current evidence on how investors navigate climate risk, legal liability, and portfolio strategy by reassessing the financial role of brown assets in high carbon transition contexts. The review finds that carbon intensive assets, traditionally viewed as stranded or declining, may provide conditional hedging value when policy trajectories remain uncertain, green technologies are not yet fully scalable, and transition risks are uneven across sectors. Legal liability emerges as a powerful driver of portfolio decisions, as fiduciaries face increasing scrutiny regarding climate disclosure, risk governance, and alignment with net zero commitments. The synthesis reveals that the strategic value of brown assets is dynamic rather than static, depending on regulatory convergence, technological maturity, and institutional investor risk preferences. Overall, the review highlights the interplay between climate related litigation pressures and investment strategy, emphasizing the need for adaptive risk assessment frameworks in a rapidly evolving transition landscape.